Phenomenologic Study of Experiences of Researchers in Kerman and Tehran Medical University about Ethics in Animal Research - M Mobasher (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: The history of biomedical research and results of valuable studies of scientists show importance of using animals in this research. The responsibility for experimental animals and concentration on animal right and welfare are moral duty of researchers. According to widespread animal use in research in our country, we explored experiences of researchers about the ethical principles of animal use in research in Kerman and Tehran University of medical sciences by phenomenologic study.METHODS: In this study, 10 experts in animal research with 15-20 years of work experience in the fields of physiology, pharmacology, biology, immunology and dentistry in Tehran and Kerman Universities of medical sciences, Iran were interviewed. Data analysis and exploitation of main themes was done based on interviews by using experimental animal guideline in Iran and themes were categorized.FINDINGS: In this study, 5 main themes were found. Theme1: more participants emphasized using minimum number of animals in their experiments except cases that they were obliged to use more animals. Theme 2: all participants explained about suitable methods of anesthesia. Theme 3: all participants knew about euthanasia methods and explained about limitations of that. Theme 4: the participants in this study emphasized on training of animal researchers. Theme 5: also, the participants stated that animal care personnel are not well trained.CONCLUSION: According to the results of this study, our expert researchers know ethical principles of animal use entirely but they can not use this knowledge because human and possession resources are limited and greatest limitation is well trained students and animal care personnel. So it is recommended to design appropriate training course according to researchers requirement for using animals in research.